Effects of tactical dimension and situational variables in throw-ins on the offensive performance in football - Casal, C. A.; Armatas, V.; Losada, J. L.; Mitrotasios, M. (PLOS ONE, 2023)
The aim of the study was to describe the usual practices in the execution of throw-ins by La Liga teams during the 2021-2022 season, identify tactical indicators related to the outcome of plays that start with a throw-in, calculate their predictive power, and finally analyse the influence of situational variables on the effectiveness of these plays. A total of 2,658 throw-ins, during 80 matches were analysed. Two UEFA PRO coaches designed an ad hoc observation instrument "Thrinfoot" and two observers coded the data after a training process. Inter and intra-observer reliability was calculated using Cohen´s Kappa coefficient, revealing almost perfect agreement. Multinomial logistic regression was applied to predict the throw-ins outcome (p<0.05). Results showed how fast throw-ins (OR = 0.7, p<0.05), without pressing (OR = 0.4, p<0.001), short and backwards (OR = 0.3, p<0.01) in the central zone (OR = 0.6, p<0.01) and made in the 16´-30´ (OR = 0.6, p<0.01), 61´-75´ (OR = 0.7, p< 0.05) periods, presented higher probabilities of continuing with possession. Match status losing>2 (OR = 4.1, p< 0.05) showed higher probabilities of success. On the other hand, throw-ins from the defensive zone presented higher probabilities of unsuccess (OR = 8.6, p<0.01) and losing possession (OR = 1.8, p<0.01). Finally, the bottom teams showed the highest probability of losing the ball. In conclusion, tactical indicators such as duration, press, distance, direction and zone were identified as key performance indicators and the situational variables team quality, match status and time influence the outcome of throw-ins. These findings provide valuable insights to coaches regarding the factors that influence the outcome of throw-ins. This allows them to design optimal strategies for both executing and defending these plays based on the game situation and their immediate aims.